2007
DOI: 10.1007/s00421-007-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-cooling procedures on intermittent-sprint exercise performance in warm conditions

Abstract: The aim of this study was to determine whether pre-cooling procedures improve both maximal sprint and sub-maximal work during intermittent-sprint exercise. Nine male rugby players performed a familiarisation session and three testing sessions of a 2 x 30-min intermittent sprint protocol, which consisted of a 15-m sprint every min separated by free-paced hard-running, jogging and walking in 32 degrees C and 30% humidity. The three sessions included a control condition, Ice-vest condition and Ice-bath/Ice-vest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 30 publications
14
121
2
Order By: Relevance
“…The benefits of whole body cryostimulation were visible not only in significant changes of peak power but also in average power, total external work, and in the time to reach Pmax. Other authors also confirm the benefits of cooling, especially in relation to short, supramaximal exercise [33]. Our research showed a significantly higher plasma lactate concentration after progressive endurance test as well as in the Wingate test after cryogenic treatments.…”
Section: O R I G I N a L P A P E R S Ijomeh 2010;23(2)supporting
confidence: 88%
See 2 more Smart Citations
“…The benefits of whole body cryostimulation were visible not only in significant changes of peak power but also in average power, total external work, and in the time to reach Pmax. Other authors also confirm the benefits of cooling, especially in relation to short, supramaximal exercise [33]. Our research showed a significantly higher plasma lactate concentration after progressive endurance test as well as in the Wingate test after cryogenic treatments.…”
Section: O R I G I N a L P A P E R S Ijomeh 2010;23(2)supporting
confidence: 88%
“…On the contrary, Banfi et al [7] demonstrated that whole-body cryotherapy had no effect on hematological values of either red blood cell count or leukocytes and platelets. A positive influence of pre-cooling procedures on submaximal bouts of exercise in warm conditions was observed by Duffield and Marino [33], yet those experiments were related to application of ice and cold water. Also, the research of Uckert & Joch [37] indicated that cooling with ice-cooling vest applied 20 min before exercise increased running endurance in warm conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is the first report of arterial [K + ] during HI int , comprising brief sprints repeated in bursts to simulate intense activity undertaken in many team sports (Bishop et al 2011 (Krustrup et al 2006;Wylie et al 2013;Mohr et al 2011;Mohr et al 2007;Duffield and Marino 2007;Mohr et al 2006;Struthers et al 1988). …”
Section: Modest Arterial K + Disturbances During High Intensity Intermentioning
confidence: 99%
“…The antecubital venous [K + ] reported during intense intermittent exercise varies, reaching 4.3 mM during squash (Struthers et al 1988), 5.1 mM during soccer (Krustrup et al 2006), and 5.5-6 mM during repeated intermittent sprint testing (Wylie et al 2013;Mohr et al 2011;Mohr et al 2007;Duffield and Marino 2007;Mohr et al 2006 O 2 peak for use on the same cycle ergometer in the subsequent experimental trials. All respiratory measurements were as previously described (Atanasovska et al 2014) .…”
Section: Introductionmentioning
confidence: 99%